Study of the Role of Customary Institutions in Government Systems in Hitu Lama State, Leihitu District, Central Maluku Regency - Latuconsina, Nurainy; Fretes, Judy De; Tehuayo, Johan (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2020)
Pemerintahan Negeri is a term used by people in Central Maluku regency in Maluku Province to state the system in the division of administrative territory at the village level. The term Negeri replaces the status of the village or kelurahan used in the regency. Pemerintahan Negeri has a spirit called Budaya Negeri (culture of Negeri). The spirit of Budaya Negeri in is a genelogical-territorial system in customary law unit immersed and used from the royal government system until now containing the characteristic and beliefs of local customs. In this system, the leader of the village or Negeri who runs the government is called Bapak Raja (The King). The position of Bapak Raja as the leader of the village-governmental system has been running for a long time. The culture of Pemerintahan Negeri is still believed to be the model of the customary government system in Central Maluku. This study aims to determine the role of costumary institutions in the Pemerintahan Negeri system in Hitu Lama, Central Maluku Regency. This study uses descriptive qualitative method. Data collection techniques used are direct observations, interviews, and documents analysis. The collected data are then analysed using reduction analysis techniques, data display (data presentation) and verification (drawing conclusions). The primary data sources in this study are taken from Bapak Raja of Hitu Lama, the costumary institution of Hitu Lama named "Saniri Negeri". Meanwhile, secondary data are collected from documents of governmental which are available at various costumary institutions in Negeri-Negeri or villages in Central Maluku. Based on the results of the study, it is revealed that: First, there are a small number of villagers in the Negeri who are lack of trust and are not obedient to the existence of "Saniri Negeri" costumary institution of Hitu Lama in conducting the Negeri development planning. As a result, it has implications for the lack of good relations between the costumary institution and the villagers of Hitu Long. Second, villagers are always active in the Negeri development planning seen from their participations in public meetings as a form of conveying aspirations and ideas. Third, the decision-making always involves two governmental elements in the Negeri which are Bapak Raja and the “Saniri Negeri”. Fourth, although there are small number of villagers who are lack of trust to the “Saniri Negeri”, overall there is still harmonious communication between the “Saniri Negeri” and the villagers in carrying out their duties in the Negeri development and social community development. The communication is important because the “Saniri Negeri” holds supervisory function to oversee the implementation of Hitu Lama programs run by the official government in accordance with development plannings that have been agreed at the oublic meetings. From the results of the study, it is concluded that the “Saniri Negeri” costumary institution in Hitu Lama has crucial function in creating harmony between the Negeri government lead by Bapak Raja and the villagers in order to implement the Negeri development plannings based on its expected results.